Successful treatment of renal cell carcinoma with paraneoplastic nephrotic syndrome: a case report - Singh Singh, Arshdeep; Naranjo, Javier; Alonso, Marta; Villanego, Florentino; Amaro, Jose Manuel; Carrasco, Daniel; Salvatierra, Cristina; Mazuecos, Auxiliadora (Frontiers in Medicine, 2025)
The association of renal cell carcinoma (RCC) with paraneoplastic membranous nephropathy (MN) is rare. Accurate identification and treatment of the primary tumor can lead to resolution of nephrotic syndrome. We report the case of a 72-year-old male was referred to Nephrology due to significant proteinuria (Urine albumin-creatinine ratio 14,000 mg/g) without clinical nephrotic syndrome. Imaging revealed a nodular lesion in the left kidney, compatible with the diagnosis of papillary renal neoplasia. A total left nephrectomy confirmed papillary RCC and MN. Post-surgery, renal function initially declined but stabilized, with proteinuria significantly reduced by the latest follow-up. Review of 20 cases of nephrotic syndrome associated with RCC revealed that MN was the most frequent underlying nephrosis. MN is frequently associated with solid tumors, but its link with RCC is uncommon. In our review, clear cell carcinoma (CCC) was the most prevalent RCC subtype linked with MN. Early cancer screening in MN patients can uncover occult malignancies, facilitating timely treatment. RCC-associated MN is rare but should be considered in patients presenting with nephrotic syndrome. Surgical resection of the RCC can lead to resolution of the associated nephropathy. This case underscores the importance of thorough cancer screening in patients with unexplained nephrotic syndrome.